Les traditions judaïsantes et la sainteté en héritage chez les premiers ascètes et dévots de l’islam - Kabira Masotta (Cahiers d'Études du Religieux- Recherches Interdisciplinaires)
The technical term isrā’iliyyāt refers to narratives stemming from Jewish literature (canonical scriptures and their commentaries as well as apocrypha) which deal with cosmogony and stories of Patriarchs and Prophets of the Sons of Israel, the “Banū Isrā’īl”. These narratives are used both as a contextual framework for the Biblical characters mentioned in the Quran, and as a source of reference in Quranic exegesis, hadith, historiography and hagiography. In the 11th century hagiographical corpus entitled Ḥilyat al-awliyā’ wa-ṭabaqāt al-aṣfiyā’ which deals with the lives of saints from the three first centuries of Islam, they are a major hermeneutical source for the first generations of Muslim devout men. In this article, we will look into the latter’s interpretative workings as well as the relationship between these Jewish-inspired traditions and the concept of holiness known as walāya.